Nurse Therapeutic Communication in the Inpatient Room - Ginting, Amnita; Karo, Mestiana Br; Pakpahan, Rotua (Indonesian Journal of Global Health Research, 2024)
Therapeutic communication is a way build a relationship in the process of exchanging information, feelings and thoughts to form a more intimate relationship during therapy. Nurses provide support and information to patients and pay attention to their professionalism. This is very infortant for medical personnel to have skills in implementing therapeutic communication in order to successfully implement therapeutic communication. . Method: Quantitative descriptive research design, the sample in this study was 100 patients using purposive sampling technique. The instrument used was a therapeutic communication questionnaire. Results: The research results showed that the therapeutic communication of nurses in the enough category was 61 (61%) respondents, good 38 (38%) respondents and bad category 1 (1%) respondents. Conclusion: the therapeutik communication of nurses at inroom patients is in the sufficients categori, it is hoped the nurses will be able to carry out the termination phase well, carry out evaluations for each action carried out and convey to the patients a follow-up plan at the next meeting to increase the patients’s sense of trust in the nurse.